Ewing Sarcoma: An Eponym Window to History. (21st November 2010) - Cripe, Timothy P.
Abstract : Ewing sarcoma was named after James R. Ewing, an eminent American pathologist at Cornell who described the first cases in 1921. Although he is best remembered for this singular achievement, Ewing's contributions to the study of cancer were far more profound and influential. He essentially launched oncology as a discipline with the publication of his seminal textbook and founded the major American cancer societies that exist today. His vision of comprehensive cancer centers still drives our research infrastructure. Since his initial report, these organizations have helped us achieve numerous milestones in understanding and treating patients with Ewing sarcoma.